Linking the Uganda Agriculture LTS with NDCs, NAP-Ag and negotiations on Global Goal on Adaptation - Cramer, Laura K. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A presentation on linking long-term, low-emission, and climate-resilient development strategies (LTSs) to the short-term and long-term goals of Nationally Determined Contributions and National Adaptation Plans to ensure policy coherence and alignment. Presented by Laura Cramer at the agriculture sector long-term strategy stakeholder validation meeting in Jinja, Uganda, on May 16, 2023.